(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Pregnancy in patients with end-stage renal disease is a rare condition that requires multidisciplinary care. Severe preeclampsia can lead to severe maternal and fetal morbidity and mortality, including kidney failure and intrauterine growth restriction. Case presentation: A 31-year-old para 1 gravida 2 presented to KNH Othaya at 29 weeks of gestation with elevated blood pressure and generally feeling unwell. She had been transferred from a different facility where she had been found to have a small for gestational age pregnancy. She had been started on methyldopa and nifedipine. Her admission blood pressure was 166/102mmHg, and urinalysis revealed severe proteinuria (+++). She denied any severe features. On examination, the patient was sick-looking, and her feet were swollen. Her abdomen was soft, and her fundal height was 24 weeks. An obstetric ultrasound scan showed an estimated fetal weight of 200g and gestational age of 24 weeks. Her biophysical profile was 6/8 with a reduced amniotic fluid index. Her hemoglobin was 10g/dL, platelets of 132x10^9/L, normal liver function test, urea 30 mg/dL, and creatinine 700 umol/L. She was admitted and started on magnesium sulfate and corticosteroids. She was also reviewed by a nephrologist and started on hemodialysis. Despite twice-weekly dialysis, there was no recovery of renal function and no significant change in fetal growth with fortnightly obstetric scans. Her general condition remained the same and her blood pressure labile, requiring constant adjustment of antihypertensives. After six weeks, a multidisciplinary decision was taken to terminate the pregnancy to save the mother’s life. This was discussed with her parents and her partner, and prostaglandin induction was successfully undertaken. Her kidneys recovered subsequently, dialysis was stopped, and she was discharged home. Conclusion: This case illustrates the importance of a multidisciplinary team in the management of antenatal renal failure secondary to preeclampsia.